Two new synanthropic species of Anyphaena Sundevall (Araneae: Anyphaenidae) associated to houses in Mexico City - Durán-Barrón, César G.; Pérez, Tila M.; Brescovit, Antonio D. (Zootaxa, 2016)
The family Anyphaenidae is composed by 56 genera and 542 species worldwide (World Spider Catalog 2015). These spiders, known as “ghost spiders”, are wandering hunters living in a variety of environments, from forests to deserts, and can be quite abundant in different crops such as cotton, sorghum and rice (Brescovit 1996; Young & Edwards 1990; Taylor & Pfannenstiel 2008). They typically live on vegetation, among dead leaves or under loose bark and rocks (Richman & Ubick 2005) but synanthropic associations have been reported for a few species (Jiménez 1998; Guarisco 1999; Durán-Barrón et al. 2009). The genus Anyphaena has 81 species widely distributed in Asia, Central Europe, North America and Mexico (Brescovit 1996; Richman & Ubick 2005; World Spider Catalog 2015). The species from Noth America and Mexico were revised by Platnick (1974) who recognized four species groups (accentuata, celer, pectorosa and pacifica). Platnick (1977), Platnick & Lau (1975) and Brescovit & Lise (1989) complemented the revision of the genus in Central America. Presently, there are 27 species of Anyphaena recorded in Mexico (World Spider Catalog 2015), 24 of them from the celer group. Here, two new species of Anyphaena are described based in material collected during an inventory of spiders associated to houses in Mexico City, carried out by Durán-Barrón et al. (2009). Both species have the diagnostic characters of the members of the pacifica group as defined by Platnick (1974), such as the lack of leg coxal spurs and the presence of a lightly sclerotized atrium in the female epigynum. These species represent the first record of the pacifica group in Mexico. The occurrence of Anyphaenidae associated to houses was reported in Mexico by Durán-Barrón et al. (2009), who recorded Anyphaena obregon Platnick & Lau, 1975 and Hibana futilis (Banks, 1898) as frequent inhabitants inside houses. The species herein described are reported solely from urban areas and can be also characterized as frequent in these anthropic environments.